TEKNIK PEMASANGAN PERANGKAT MESIN KAPAL PERIKANAN - Ahmad, Muchtar; Habibie, Ied; Nofrizal, Nofrizal (Jurnal Perikanan dan Kelautan, 2009)
Effort for obtaining effective engine power of fishing vessel and improve thework condition comfortableness on the vessel believed to increase productivity andefficiency of fishing vessel. Assembling of engine accessories effected output ofengine power optimally. Therefore, based on mechanism system analysis of fishingvessel was conducted a study on assembling of engine accessories, such as exhaustpipe, electricity system, rudder and its size calculation method.